Light Showing from The Reconstruction of Prasat Puei Noi, Puea Noi District, Khon Kaen Provine, to Promote Cultural Tourism - Wongpongkham, Hawa; Wongpongkham, Niyom (Academic and Research Journal of Liberal Arts (Online), 2024)
This article aimed to study the light from the reconstruction of Prasat Puei Noi, Khon Kaen province, to promote cultural tourism using a qualitative research process. The research tools consisted of surveys and interviews. The data was compiled from documents and field research and analyzed using the creation virtual reality model and the concept of cultural tourism. The result was presented in descriptive analysis. The result from the study of the reconstruction of Prasat Puei Noi, Khon Kaen province to promote cultural tourism revealed that the lighting show was based on the reconstruction of Prasat Puei Noi, Khon Kaen province on an actual scale (1:1). The study was a continuity of the Reconstruction of the Khmer Architecture in Khon Kaen province project which uses new technology to highlight the aesthetic of this ancient site. The project was considered another form of arts and culture revitalization, causing tourists and the audience of the light show of the ancient site to have more understanding of the site, as well as experiencing the virtual light show. This project helped improve Khon Kaen tourist sites to a more international level, creating new perspectives for the tourists and communities, as well as the general public, promoting cultural tourism, and creating imagination for the viewers. The data related to the light show was also compiled in the form of a documentary.